Kuasa-kuasa, tugas dan peranan pendakwa syarie (Kelantan Darul Naim) - Kamarudin, Abdul Rani; Abas, Afridah (LexisNexis, 2012)
This article discussed on the power and role of the Syarie Prosecutor based on the Islamic Enactments of the State of Kelantan. It further elaborated how that objectives are achieved, and suggestions to enhance them even further.